PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN SIKAP RELIGIUS SISWA PADA ASPEK ISLAM - Hasanah, Siti Nur Hidayatul; Zainuddin, Mohammad Riza (IMTIYAZ: Jurnal Ilmu Keislaman, 2023)
Schools as a place to educate the nation's next generation are very important in seeking to improve the religious attitude or character of students, especially in the Islamic aspect. At present, Islamic religious education in schools is considered less successful in changing the attitudes and behavior of the diversity of students and building the morals and ethics of the nation. The reality of student behavior that is very real is the increasing number of students involved in brawls between students, drug association, theft, promiscuity and so on. The role of the teacher at school is very important in helping students to improve their religious character through various learning activities carried out at school. The religious attitude in the Islamic aspect concerns the frequency and intensity of the implementation of worship which determines, for example, prayer, fasting and zakat. The role of the teacher in shaping or improving students' religious attitudes to the Islamic aspect includes: the teacher must be able to be a good educator, the teacher can be a good teacher, the teacher becomes a guide, and most importantly the teacher can be a model and role model for his students.